2002
DOI: 10.1089/109493102753770507
|View full text |Cite
|
Sign up to set email alerts
|

"On the Internet No One Knows I'm an Introvert": Extroversion, Neuroticism, and Internet Interaction

Abstract: Social communication is one of the most common reasons for using the Internet. This paper examines how the personality characteristics of the user affect the meaning and importance of Internet social interaction in comparison with "real life," face-to-face interactions. Forty subjects all of whom were familiar with using "chat" participated in this study. After a at" session, they were instructed to answer several questionnaires. It was found that introverted and neurotic people locate their "real me" on the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
228
7
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(257 citation statements)
references
References 6 publications
14
228
7
8
Order By: Relevance
“…Past studies have shown very conflicting results with Extraversion and online communication (see Table 1). We find that in contrast to Amichai-Hamburger et al (2002), who found that Introverts prefer online communication, Extraverts, who seek stimulation from other people, actually prefer online communication. Orchard and Fullwood (2010) propose that Extraverts may use the Internet for increasing their offline social networks whereas Introverts may use the Internet to escape their offline personas.…”
Section: Communicationcontrasting
confidence: 83%
See 3 more Smart Citations
“…Past studies have shown very conflicting results with Extraversion and online communication (see Table 1). We find that in contrast to Amichai-Hamburger et al (2002), who found that Introverts prefer online communication, Extraverts, who seek stimulation from other people, actually prefer online communication. Orchard and Fullwood (2010) propose that Extraverts may use the Internet for increasing their offline social networks whereas Introverts may use the Internet to escape their offline personas.…”
Section: Communicationcontrasting
confidence: 83%
“…With adolescents, Extraversion was correlated with Internet communication (Wolfradt & Doll, 2001). In contrast, Extroversion was found to be negatively correlated with feeling comfortable communicating online (Amiel & Sargent, 2004) and with using online chat (Anolli et al, 2005), also in contrast to the claim of Amichai-Hamburger et al (2002).…”
Section: Communicationmentioning
confidence: 79%
See 2 more Smart Citations
“…Individuals" self-consciousness disappears, sense of time becomes distorted, and the resulting state of mind is extremely gratifying when he/she is in a state of flow (Hoffman and Novak, 1996). Introverted people locate their "real me" on the internet, while extroverted people locate their "real me" through traditional social interaction [15].…”
Section: Mediating Effectsmentioning
confidence: 99%